Projeto de controlador para sistemas discretos considerando atraso de comunicação variante no tempo utilizando princípios da dualidade - Ernesto, Jackson Gonçalves (2018)
In this work a technique for the synthesis of state-feedback gains, capable of stabilizing discrete- time systems affected by time-varying uncertain delays, is proposed. The technique extends another synthesis condition presented in the literature, which is based on the application of a Lyapunov-Krasovskii function to generate a set of linear matrix inequalities (LMIs) and equality constraints. The method proposed is based on the dual representation of the delayed system, resulting in a LMI condition free of the equality constraints, thus reducing the complexity of the technique. A simulation example and an conservatism analysis illustrates the validity of the proposed method.